Obstetric evidence based guidelines - Berghella, Vincenzo (Boca Raton : CRC Press, 2021)
"This new edition of an acclaimed text reviews the evidence for best practice in obstetrics, to present the reader with the right information, with appropriate use of proven interventions and avoidance of ineffectual or harmful ones. The information is presented in the right format by summarizing evidence succinctly and clearly in tables and algorithms. The aim is to inform the clinician, to reduce errors and "to make it easy to do it right.""--
Includes bibliographical references and index.
Keywords: Pregnancy; Delivery, Obstetric -- methods; Evidence-Based Medicine; Pregnancy Complications; Prenatal Care -- methods; Practice Guideline